Visualization of anatomical structures in the carpal region of the horse using cone beam computed tomography in comparison with conventional multidetector computed tomography - Hagenbach, M.; Bierau, J.; Cruz, A. M.; Koch, C.; Manso-Díaz, G.; Büttner, K.; Staszyk, C.; Röcken, M.; Justus Liebig University Giessen (My University, 2024)
Introduction: In the diagnostics of orthopedic diseases in the horse, diagnostic imaging often plays a decisive role. Cone beam computed tomography (CBCT) imaging is used in both human and small animal medicine and becoming increasingly popular. To see whether CBCT imaging can be useful in the diagnosis of orthopedic diseases of the carpal region of the horse and to explore possible limitations we compared CBCT images with multidetector computed tomography (MDCT) images of the carpal region of equine cadaveric specimens. Materials and methods: Twenty-eight forelimbs from fifteen horses, slaughtered for reasons unrelated to this study, were examined. Native and contrast enhanced CBCT and MDCT scans were performed. Anatomical structures were blindly evaluated by three independent experienced observers using a visual scoring system previously reported and adapted to the equine carpal region. A descriptive evaluation was carried out as well as Spearman’s rank correlation and interobserver agreement was shown by percent agreement (PA). Results: Visualization of osseous structures was excellent in both MDCT and CBCT. Articular cartilage could only be assessed in contrast enhanced scans whereby MDCT showed a slightly better visualization than CBCT. Soft tissue structures were generally difficult to assess. An exception were the medial and lateral palmar intercarpal ligament, which could not be visualized in native but were well visualized in contrast enhanced scans in both MDCT and CBCT images. Discussion/conclusion: For the evaluation of osseous structures and some intraarticular ligaments after contrast enhancement, CBCT serves as a reliable diagnostic imaging modality for the equine carpal region. However, soft tissue structures and cartilage are imaged more reliably using MDCT.
Keywords: ddc:630